Basophilic histamine content and release during venom immunotherapy: Insights by flow cytometry1. Issue 3 (28th February 2013) - Nullens, S.; Sabato, V.; Faber, M.; Leysen, J.; Bridts, C. H.; De Clerck, L. S.; Falcone, F. H.; Maurer, M.; Ebo, D. G.
Abstract: Background: Despite the efficiency of venom immunotherapy, the effects on basophils and mast cells remain incompletely understood and probably vary according to the treatment phase. Objectives: To study the effect of build‐up and maintenance venom immunotherapy on individual basophils. Methods: Intracellular histamine and its release was analyzed flow cytometrically by a new enzyme‐affinity method using diamine oxidase conjugated to laser‐excitable fluorochromes. Phenotyping of cells included flow cytometric quantification of CD63 and CD203c. Analyses of basophil activation experiments were performed before the start of treatment, after build‐up therapy and during maintenance therapy. Results: Before the start of therapy, patients demonstrated significantly higher numbers of basophils when compared with stung control individuals. At the end of build‐up therapy a decrease of basophil numbers was observed, whereas during maintenance therapy basophil counts returned to pretreatment values. Before the start of therapy, the intracellular histamine content per cell in patients was significantly higher when compared with stung control individuals. During maintenance therapy intracellular histamine content decreased to values observed in stung control individuals. In addition, maintenance therapy lowered the net release of histamine per cell in response to optimal stimulation with wasp venom. Conclusions: We introduce a novel technique that enables to assess the effects of venom immunotherapy on basophils. This new technique may help to monitor treatment effects in individual patients and could aid in the development of more efficient and better tolerated immunotherapy protocols. © 2013 International Clinical Cytometry Society